Protective effects of glycerol and xylitol in keratinocytes exposed to hyperosmotic stress - Szél E; Danis J; Sőrés E; Tóth D; Korponyai C; Degovics D; Prorok J; Acsai K; Dikstein S; Kemény L; Erős G (Dove Medical Press, 2019)
Edit Szél,1 Judit Danis,2 Evelin Sőrés,1 Dániel Tóth,3 Csilla Korponyai,1 Döníz Degovics,1 János Prorok,3 Károly Acsai,3 Shabtay Dikstein,4 Lajos Kemény,1,2 Gábor Erős11Department of Dermatology and Allergology, University of Szeged, Szeged, Hungary; 2MTA-SZTE Dermatological Research Group, Szeged, Hungary; 3Department of Pharmacology and Pharmacotherapy, University of Szeged, Szeged, Hungary; 4Unit of Cell Pharmacology, Hebrew University, Jerusalem, IsraelPurpose: Our goal was to study whether glycerol and xylitol provide protection against osmotic stress in keratinocytes.Methods: The experiments were performed on HaCaT keratinocytes. Hyperosmotic stress was induced by the addition of sorbitol (450, 500 and 600 mOsm). Both polyols were applied at two different concentrations (glycerol: 0.027% and 0.27%, xylitol: 0.045% and 0.45%). Cellular viability and cytotoxicity were assessed, intracellular Ca2+ concentration was measured, and the RNA expression of inflammatory cytokines was determined by means of PCR. Differences among groups were analyzed with one-way ANOVA and Holm-Sidak post-hoc test. When the normality test failed, Kruskal–Wallis one-way analysis of variance on ranks, followed by Dunn’s method for pairwise multiple comparison was performed.Results: The higher concentrations of the polyols were effective. Glycerol ameliorated the cellular viability while xylitol prevented the rapid Ca2+ signal. Both polyols suppressed the expression of IL-1α but only glycerol decreased the expression of IL-1β and NFAT5.Conclusions: Glycerol and xylitol protect keratinocytes against osmotic stress. Despite their similar chemical structure, the effect of these polyols displayed differences. Hence, joint application of glycerol and xylitol may be a useful therapeutic approach for different skin disorders.Keywords: hyperosmotic stress, glycerol, xylitol, intracellular calcium concentration